The Use of Digital Media in Arabic Language Learning at MTs Raudhatul Hasanah Tanjung Jabung Timur - Wiji Hastutik; M. Syukron Maksum (Universitas Muhammadiyah Enrekang, 2026)
This study aims to analyze the use of digital media in Arabic language learning at MTs Raudhatul Hasanah Tanjung Jabung Timur and its influence on student motivation and learning outcomes. The development of educational technology requires teachers to be able to utilize digital media as an effective, interactive, and appropriate learning tool in accordance with the characteristics of the digital generation. However, in practice, Arabic learning in madrassas is still dominated by conventional methods that cause low student motivation to learn. This study uses a mixed method approach with a sequential explanatory design. The research sample consisted of 56 grade VIII students and 2 Arabic teachers. Data collection techniques use observation, learning motivation questionnaires, interviews, documentation, and learning outcome tests. Data analysis was carried out through descriptive statistics, simple regression tests, and interactive qualitative analysis. The results show that the use of digital media such as interactive PowerPoint, learning videos, application-based quizzes, and online learning platforms has a positive influence on student motivation and learning outcomes. The average value of learning motivation increased from 65.2 to 84.6, while the average learning outcome increased from 68.4 to 86.1. The results of the regression test showed a significance value of 0.000 < 0.05 which means that digital media has a significant effect on Arabic language learning. The novelty of this research lies in the use of digital media based on the context of rural madrasas with limited facilities but still effective through a simple and adaptive approach. This study recommends strengthening teachers' digital literacy to improve the quality of Arabic learning in madrasas.